Effects of dietary prickly ash seeds supplementation on muscle development and volatile compounds of Hu sheep - Qiao Li; Zilong Liu; Yi Wu; Chunhui Wang; Xueyi Ma; Youji Ma (Food Chemistry: Molecular Sciences, 2025)
Prickly ash seeds (PAS), a nutrient-rich by-product, show potential as a sustainable feed for Hu sheep. The current study aims to explore the effects of dietary supplementation with PAS on muscle development and volatile compounds of Hu sheep through multi-omics analysis. The increased muscle fiber diameter and cross-sectional area was associated with dietary supplementation with PAS compared with the CK group (P < 0.05). Transcriptome analysis showed that ACTC1, SERPINA3, COX2, MYBPH, FMOD, and KLHL34 were key differentially expressed genes (DEGs) involved in muscle growth and development, and played a role through oxidative phosphorylation, TCA cycle, fatty acid metabolism, and tryptophan metabolism. The combined analysis of transcriptome and volatile metabolomics showed that LEP, ADCY1, TMEM54, COX2, PCK1, and CPT1A may play an important regulatory role in the production of volatile compounds such as cetene, dodecanal, 2,6-dodecadien-1-al, palmitoleic acid, dodecanoic acid, ethyl ester by participating in lipid metabolism. In summary, PAS demonstrates promise for Hu sheep production, enhancing muscle development and influencing muscle flavor by modulating fatty acid metabolism-related genes